2021
DOI: 10.21831/ltr.v20i2.34478
|View full text |Cite
|
Sign up to set email alerts
|

"Pro-Whom?": A Critical Discourse Analysis of President Donald Trump's Immigration Policy Speeches

Abstract: Immigration has been an integral part of American history, drawing the attention of every one to the country's presidents, including the incumbent Donald J. Trump. President Trump is known to have been quite "frank" in conveying his views of immigrants and immigration, as well as his perspectives regarding their positive and negative aspects. This qualitative descriptive study aims to analyze the view about immigrants and immigration conveyed through President Trump's speeches on immigration policy. Using Fair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Thus, this condition was similar to Risma who used the word "kita" in order to persuade the staffs. In Aini, Baskoro, & Firmonasari (2021) also found that in political speech by President Trump, the ideology to influence audiences were gone through intertextuality and interdiscursivity. Both ways indicated his position, his stance, and his allies.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, this condition was similar to Risma who used the word "kita" in order to persuade the staffs. In Aini, Baskoro, & Firmonasari (2021) also found that in political speech by President Trump, the ideology to influence audiences were gone through intertextuality and interdiscursivity. Both ways indicated his position, his stance, and his allies.…”
Section: Discussionmentioning
confidence: 97%